2022
DOI: 10.3390/chemosensors10060210
|View full text |Cite
|
Sign up to set email alerts
|

Isothermal Amplification and Lateral Flow Nucleic Acid Test for the Detection of Shiga Toxin-Producing Bacteria for Food Monitoring

Abstract: Foodborne bacteria have persisted as a significant threat to public health and to the food and agriculture industry. Due to the widespread impact of these pathogens, there has been a push for the development of strategies that can rapidly detect foodborne bacteria on-site. Shiga toxin-producing E. coli strains (such as E. coli O157:H7, E. coli O121, and E. coli O26) from contaminated food have been a major concern. They carry genes stx1 and/or stx2 that produce two toxins, Shiga toxin 1 and Shiga toxin 2, whic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 51 publications
0
2
0
Order By: Relevance
“…In recent studies, researchers have used RPA and combined it with LFA systems, fluorescent dyes, fluorescent probes, or CRISPR/Cas-based technology to detect pathogens in food samples ( Cai et al, 2021 , Chen et al, 2021 , Jin et al, 2022 , Liu et al, 2022a , Ma et al, 2020 , Mao et al, 2022 , Petrucci et al, 2022 , Tian et al, 2021 , Wang et al, 2021 , Wang et al, 2022b ) ( Table S4 ). For example, Ma et al (2020) utilized RPA in combination with a lateral flow dipstick to identify various pathogens in different types of food samples.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent studies, researchers have used RPA and combined it with LFA systems, fluorescent dyes, fluorescent probes, or CRISPR/Cas-based technology to detect pathogens in food samples ( Cai et al, 2021 , Chen et al, 2021 , Jin et al, 2022 , Liu et al, 2022a , Ma et al, 2020 , Mao et al, 2022 , Petrucci et al, 2022 , Tian et al, 2021 , Wang et al, 2021 , Wang et al, 2022b ) ( Table S4 ). For example, Ma et al (2020) utilized RPA in combination with a lateral flow dipstick to identify various pathogens in different types of food samples.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%
“… Wang et al (2021) used a similar approach to detect V. cholerae and V. vulnificus in shrimps and found that these pathogens could be detected at a concentration of 1 cfu/10 g after 4 h of enrichment. This approach has also been used by Petrucci et al (2022) to detect E. coli O157:H7 in chicken meat and they found that this pathogen could be detected at a concentration of 10 cfu/mL after enriching their samples for 10 min.…”
Section: Recent Advances In Naa-based Methodsmentioning
confidence: 99%